Association of polymorphisms in PRKCI gene and risk of prostate cancer in a sample of Iranian Population - Hashemi, M; Shahkar, G; Simforoosh, N; Basiri, A; Ziaee, S A M; Narouie, B; Taheri, M (Cellular and Molecular Biology, 2015)
The atypical protein kinase C iota (aPKCÎ¹) is an oncoprotein encoded by the PRKCI gene. It has been reported to play multifunctional roles in cellular maintenance, cell proliferation, survival, differentiation and apoptosis. In the present study we aimed to assess the impact of PRKCI rs546950 C>T and rs4955720 C>A polymorphisms on prostate cancer (PCa) risk in a sample of Iranian population. This case-control study was done on 169 patients with pathologically confirmed PCa and 182 benign prostatic hyperplasia (BPH). The PCR-RFLP method was used for detection rs546950 C>T and rs4955720 C>A polymorphisms. Our findings showed that rs546950 polymorphism of PRKCI decreased the risk of PCa in codominant (OR=0.35, 95%CI=0.19-0.64, P<0.001, CT vs CC) and dominant (OR=0.39, 95%CI=0.22-0.69, P=0.001, CT+TT vs CC) inheritance model tested. No significant association was found between rs4955720 C>A polymorphism and PCa. In the combined analysis of these two variants subjects carrying CT/CC, CT/CA, TT/AA and CT/AA significantly decreased the risk of PCa in comparison with rs546950 CC/rs4955720 CC genotype. Haplotype analysis indicated that rs546950T/rs4955720A decreased the risk of PCa compared to CC. In conclusion, the results revealed that PRKCI rs546950 variant decreased the risk of PCa in an Iranian population. Further studies with larger sample sizes and different ethnicities are required to confirm our findings.